HPLC-ESI-MS and GC-EI-MS identification and quantitation of polyphenolics and alkaloids in Moroccan Jujube Honeys - Khallouki, Farid; Akdad, Mourad; Bouddine, Toufik; Hajji, Lhoussain; Owen, Robert (Journal of apicultural science, 2020)
Abstract The aim of this study was to determine the phytochemical content of Moroccan Jujube Honey and to establish the principal components of this staple Moroccan food, which contributes health benefit for the local population. Total phytochemical compounds as determined by analytical HPLC-ESI-MS in the honey extracts were 29.39±5.21 mg/kg (range 16.64-42.16) wet weight. The individual phytochemical compounds definitively identified by HPLC-DAD-ESI-MS in the Jujube honeys were the alkaloids: (I) 4-hydroxyquinoline glucoside, (II) 4-hydroxyquinoline and (V) kynurenic acid (17.66±0.87 mg/kg), and the phenolic compounds: (III) p-hydroxybenzoic acid, (IV) caffeic acid and (VI) methyl syringate (11.73±0.50 mg/kg). The structures were confirmed by GC-EI-MS apart from 4-hydroxyquinoline-glucoside. The major components were methyl syringate (8.34±2.49 mg/kg), 4-hydroxyquinoline (6.61±3.23 mg/kg) and kynurenic acid (6.56±0.97 mg/kg). The mean content of polyphenolic compounds (11.73±0.50 mg/kg) of Moroccan Jujube honeys compared favorably with those described for six Chinese Jujube honeys (2.49 mg/kg), five commercial Jujube honeys from different countries (0.92 mg/kg) and twelve Jujube honeys from Yemen (25.71 mg/kg). Reference studies did not identify alkaloids as components of Jujube honey, and therefore the phytochemical profile of Moroccan Jujube honey appears to be unique.
Gesehen am 24.02.2021